2016
DOI: 10.1027/1015-5759/a000336
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Vignettes

Abstract: Abstract. Individuals differ in the way they use rating scales to describe themselves, and these differences are particularly pronounced in children and early adolescents. One promising remedy is to correct (or ''anchor'') an individual's responses according to the way they use the scale when they rate an anchoring vignette (a set of hypothetical targets differing on the attribute of interest). Studying adolescents' self-reports of their socio-emotional attributes, we compared traditional self-report scores wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
3
20
0
2
Order By: Relevance
“…However, the individual-level correlations of rescaled scale scores of one particular scale based on target set of vignettes and nontarget set of vignettes ranged from .440 to .482, and the country-level correlations ranged from .509 to .721. The correlations among different sets of vignettes are not strong enough to conclude that one set of vignettes would work for the rescaling of different target constructs, which speaks against any one-size-fits-all application of vignettes (e.g., Primi, Zanon, Santos, De Fruyt, & John, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the individual-level correlations of rescaled scale scores of one particular scale based on target set of vignettes and nontarget set of vignettes ranged from .440 to .482, and the country-level correlations ranged from .509 to .721. The correlations among different sets of vignettes are not strong enough to conclude that one set of vignettes would work for the rescaling of different target constructs, which speaks against any one-size-fits-all application of vignettes (e.g., Primi, Zanon, Santos, De Fruyt, & John, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The unadjusted negative relationship was the misleading result of reference bias. In addition, Primi et al (2016) found that anchoring vignettes improved internal consistency (reliability) for measures of socioemotional skills, that is, it improved the extent to which a group of items hung together. Source: The conscientiousness ranks come from Schmitt et al (2007).…”
Section: Reference Biasmentioning
confidence: 99%
“…We control the response bias and acquiescence using four inverted items (two related to the task and two to the context) besides anchoring vignettes. A study by Primi et al (2016) indicated that the anchoring vignettes help in the control of the self-style response. Thus, for this study, three vignettes were created, describing examples of individuals with high, medium, and low job performance.…”
Section: Instrumentmentioning
confidence: 99%
“…Moreover, as is well known, the responses given to this type of self-reported scale are influenced by the subject's response style, which can lead to bias in the research results that use them (Primi et al, 2016). One threat is the acquiescence, also known as the "yea-saying" effect, which concept is related to the inclination to endorse positive categories of a Likert scale despite the item content.…”
Section: Introductionmentioning
confidence: 99%